SIGNIFICANCE OF PHRASEOLOGICAL UNITS IN THE DEVELOPMENT OF LITERATURE - Daminova Xolisxon (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article analyzes the cases of violation of the existing rules and norms when using phraseological units in oral and written speech. It also discusses the types of phraseological rules that exist and their place in speech. The usage of phraseological units in speech, explain their usage according to national and cultural universality, differential and paradigmatic features, ways of transition from folklore to literary language, semantic properties, artistic and methodological possibilities, problems of translation in terms of form and meaning, compelling of a dictionary suitable for modern linguistics and the importance of covering their place in the national language.